Beit Hillel i Beit Shammai - dwa oblicza szkoły rabinackiej - Rabiej, Stanisław (Studia Oecumenica, 2012)
These two great scholars born a generation or two before the beginning of the Common Era are usually discussed together and contrasted with each other, because they were contemporaries and the leaders of two opposing schools of thought (known as Ñhousesî). The Talmud records over 300 differences of opinion between Beit Hillel (the House of Hillel) and Beit Shammai (the House of Shammai). In almost every one of these disputes, Hillelís view prevailed. Rabbi Hillel was born to a wealthy family in Babylonia, but came to Jerusalem without the financial support of his family and supported himself as a woodcutter. It is said that he lived in such great poverty that he was sometimes unable to pay the admission fee to study Torah, and because of him that fee was abolished. He was known for his kindness, his gentleness, and his concern for humanity. One of his most famous sayings, recorded in Pirkei Avot (Ethics of the Fathers, a tractate of the Mishnah), is ÑIf I am not for myself, then who will be for me? And if I am only for myself, then what am I? And if not now, when?î The Hillel organization, a network of Jewish college student organizations, is named for him. Rabbi Shammai was an engineer, known for the strictness of his views. The Talmud tells that a gentile came to Shammai saying that he would convert to Judaism if Shammai could teach him the whole Torah in the time that he could stand on one foot. Shammai drove him away with a builder's measuring stick! Hillel, on the other hand, converted the gentile by telling him, ÑThat which is hateful to you, do not do to your neighbour. That is the whole Torah; the rest is commentary. Beit Hillel and Beit Shammai represented the culture of debate that characterized that period and exists until today in the Jewish Law. Despite that many differences existed between the houses they were friends and sometime we could see marriages between people from those two houses. The culture of disagreement that exists until today can be summed up in these words: ìAny dispute which is in the name of heaven (meaning: for learning and teaching) ñ should be taken place. And those who are not in Heaven ñ should not be taken place. What is the dispute in the name of heaven? The controversy between Hillel and Shammaiî.